ANALYSIS OF LEARNING DIFFICULTIES WITH FRACTIONS IN THREE AFRICAN COUNTRIES: FOCUSING ON THE SCOPE, SEQUENCE AND MODELS OF FRACTIONS - Kusaka, Satoshi (African Journal of Education and Practice, 2021)
Purpose: This study aims to compare and analyze learning content with regard to fractions, the order in which that content is taught in primary school mathematics curricula, and how it is presented in textbooks in three eastern and southern African countries, Zambia, Ethiopia, and Mozambique as well as to clarify the characteristics of the instruction concerning fraction in each of these countries. Methodology: Firstly, we refer to the curriculum to extract information about the learning contents and their order in each grade. Secondly, concerning the meaning of fractions, we refer to the textbooks since we cannot clearly judge from the description in the curriculum. Thirdly, we focus on the common points and differences among the three countries and analyze the causes of difficulty in learning fractions. Findings: There is a significant discrepancy between the grades in learning fractions among the three countries. In addition, the learning order differs to a certain degree. A common feature of the three countries regarding the order is the multiplication and division of fractions. For all three countries, while the addition and subtraction of fractions and types of fractions are handled separately by different grades, the multiplication and division are all taught in one grade. Further, how the meaning of fractions is taught is common to all three countries. In all the countries, the part-whole concept of fractions is mainly employed, and the fraction as measurement concept is not taught at all. Unfortunately, since children learn without considering fractions as measurements, their understanding of fractions will be limited. Unique contribution to theory, practice, and policy: Regarding fraction, basic research on the teaching content and their order in African countries have not been conducted extensively. While improving the quality of education is a common goal globally, it is paramount to analyze the difficulty in learning fractions from the perspectives of the intended curriculum and textbook. The result will be the implication for revising the curriculum and suggestions for teaching fractions.